The effect of intellectual capital, size, leverage, and liquidity on company value in manufacturing companies listed on Indonesia Stock Exchange (Lighthouse Publishing, 2022)
The rapid growth of technology and information can provide opportunities and also threats to the sustainability of a company. Therefore, companies must change their management patterns in order to take advantage of technological advances and strategies to compete in various markets, as well as maintain a competitive advantage by focusing on operational and financial activities. The company's goal is to maximize the wealth of shareholders by maximizing the value of the company. This study aims to provide empirical evidence related to the influence of intellectual capital, size, leverage, and liquidity on company value. The sample in this study was comprised of 84 manufacturing companies listed on the Indonesian stock exchange in 2018-2020. The analytical tool used in this study is a multiple regression model. The results of hypothesis testing with multiple regression analysis using the SPSS 26 application showed that intellectual capital, size, leverage, and company age control variables had a significant effect on company value. Meanwhile, liquidity has no significant effect on the value of the company. This study made several contributions to theory and methodology. This reinforces previous research on the value of the company. This research is expected to be used as input to evaluate companies related to intellectual capital, size, leverage, and liquidity to increase company value. This study only used a sample of manufacturing companies registered on the IDX that made a profit and only three years of research from 2018-2020. Researchers are then expected to expand the sample of all manufacturing companies listed on the IDX, including both companies that get profits and losses, and can expand the research period in order to provide better and more significant research results.